Kajian Kualitas Air dan Indeks Pencemar Wilayah Pesisir Kota Makassar (Water Quality and Pollution Index Study in the Coastal Zone Makassar City) - Suharto suharto; Funty Septiyawati Polapa; Dewi Yanuarita Satari (Jurnal Pengelolaan Perairan, 2018)
This research was conducted in two seasons, during May (dry season) to August (rainy season) to find out the water condition and the pollution index of Makassar City waters. The water sampling points represent tourism activities, ports and ponds cultivation with the number of sampling points each of 3 sub stations. water sampling was collectt using niskin bottles and analyzed in the health laboratory of South Sulawesi Province and parameters measured were BOD, Disolved Oxygen, Phosphate, Nitrate, pH, Total Phenol, Sulphate and Salinity. the result shows that Makassar City waters have Pollution index calculations are classified into mild pollution categories. Environmental parameters that still meet the quality standards for marine biota include DO, pH and Salinity, while parameters that have exceeded the quality standard include BOD, Phosphate (except dry season measurements), Phenol, Nitrate and Sulfide.Keywords : Water quality, Pollution indeks, Makassar City.